Instagram as a tool for disseminating sustainable practices: an experience report - Freitas, Yasmin Coelho de; Ferreira, Francisco de Assis; Groner, Carlos Eduardo Batista; Azevedo, Igor Tristão; Bringhenti, Jacqueline Rogéria; Korres, Adriana Marcia Nicolau (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The social isolation promoted by COVID-19 impacts the routine and habits of families with a reflection on the characteristics and generation of solid waste and consumption of natural resources. This situation has been identified as an opportunity for educational institutions to promote awareness actions with their internal and external community as a contribution to reduce such effects. In order to disseminate sustainable practices related to the daily life of the pandemic and to evaluate responses, the group of teachers and students developed activities which contributed to minimize the effects of the pandemic. The ease and speed of social media was used as a tool for actions. The methodological steps were: survey of the existing contents in the official networks of the Federal Institute of Espírito Santo related to the topic of interest, the definition of the InstagramTM social network, profile creation for the Ifes Biotechnology and Sustainability Laboratory (Labiotecs), increase of followers, creation and dissemination of content and publications analysis. The work is based on the Deming Cycle methodology in order to optimize its planning and execution. Among the results, 179 followers on the profile were reached, 10 posts were shared in the feed, 4 questionnaires and 5 polls applied until 06/17/2020. The effectiveness of the work was shown through the reach of publications and public acceptance. Also, the Deming cycle proved to be adequate and capable of being replicated.